Answer:
g(-3) = -4
Step-by-step explanation:
g(-3) = 2(-3) + 2
g(-3) = -6 +2
g(-3) = -4
Answer: −
2
±
√
13
Step-by-step explanation:
(-b±√(b²-4ac))/(2a)
Plug in and solve.
Answer:
https://www.pmschools.org/site/handlers/filedownload.ashx?moduleinstanceid=701&dataid=3612&FileName=2015%20triangle%20proofs%20answers.pdf
Step-by-step explanation:
The area of a trapezoid, A, equals h, the height of the trapezoid, times the length of base one plus the length of base two divided by two.
The perimeter of a trapezoid, P, equals the measure of base one plus the measure of base two plus the measure of leg one plus the measure of leg two
That is as simple as i can make it lol. i hope it helps some
Answer:abcd
Step-by-step explanation: